2020
DOI: 10.1002/acm2.12964
|View full text |Cite
|
Sign up to set email alerts
|

A physically meaningful relationship between R50% and PTV surface area in lung SBRT

Abstract: Purpose We propose a novel understanding of two characteristics of the planning target volume (PTV) that affect the intermediate‐dose spill in lung stereotactic body radiation therapy (SBRT) as measured by R50%. This phantom model research investigates two characteristics of the PTV that have a marked effect on the value of R50%: the mean dose deposited within the PTV (Dav) and the surface area of the PTV (SAPTV). Methods Using a phantom model provided by a CT of the IROC Thorax‐Lung Phantom® (IROC Houston QA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 25 publications
(43 reference statements)
3
9
0
Order By: Relevance
“…(), and conceptually, this analytic model should be able to account for variations in SA PTV . In fact, the model would predict larger R50% values for targets with increased SA PTV to V PTV ratios, which is consistent with the suppositions in Goldbaum et al In previous work, it was quantitatively shown that an increase in the SA PTV to V PTV ratio leads to an increase in R50% values 9 . For any given volume, the shape that corresponds to the smallest surface area is a sphere, 16 and the assumption of a spherical PTV with an isotropic dose drop‐off is central to the construction of our analytic equation for R50% [Eq.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…(), and conceptually, this analytic model should be able to account for variations in SA PTV . In fact, the model would predict larger R50% values for targets with increased SA PTV to V PTV ratios, which is consistent with the suppositions in Goldbaum et al In previous work, it was quantitatively shown that an increase in the SA PTV to V PTV ratio leads to an increase in R50% values 9 . For any given volume, the shape that corresponds to the smallest surface area is a sphere, 16 and the assumption of a spherical PTV with an isotropic dose drop‐off is central to the construction of our analytic equation for R50% [Eq.…”
Section: Discussionsupporting
confidence: 87%
“…() as zeroth order, first order, and second order terms, respectively. This complete expression is an extension of previous work that only used the zeroth order term and, as expected, significantly improves agreement for smaller PTV volumes 9,10 …”
Section: Methodssupporting
confidence: 60%
“…Utilizing an anthropomorphic head phantom study, we have applied the R50% Analytic approach devised in the lung SBRT study to cranial SRS. We demonstrate that the dependence of the achievable R50% on the SA PTV is consistent with previous lung SBRT results 12 . We test the R50% Analytic methodology on single cranial PTVs of various shapes and sizes.…”
Section: Introductionsupporting
confidence: 84%
“…We call this observed dependence of R50% on SA PTV the surface area effect. This appears to be a phenomenon not previously elucidated clearly in the literature of SRS, but it has been carefully explored in our previous work in lung SBRT 12,13 …”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation